China’s Belt and Road Initiative: A Step toward Shared Globalization - Imran Ali Sandano; Syed Faisal Hyder Shah; Irfan Ahmed Shaikh (Department of Government Studies Universitas Muhammadiyah Makassar, 2019)
Globalization is facing a major test of sustainability with growing populism and trade protectionism. West, which always endorsed for globalization has left their hands back. ‘America First’ and ‘Brexit’ has changed and challenged the original concept of globalization. China which always remained isolated from globalizations, has started to talk about globalization with its Chinese characteristics - called ‘Shared Globalization’. This study investigates that what kind of characteristics China has applied to get momentum for shared globalization. It is a descriptive study which has taken “One Belt, One Road” (BRI) as case study with the theoretical observation of shared development, shared future, and peaceful coexistence. The study has found that the new trends of shared globalization are emerging in Asia. It has created new opportunities for joint economic cooperation and deeper regional ntegration. The BRI policy framework is providing new drivers to the sustainable economic growth to the BRI counties and would work as a common cause for the world to restore the correct balance of globalization by making it more universally beneficial and inclusive. This study claims that shared globalization is pivotal to Eurasia with the shared attitude of new opportunities that could untangle the regions towards deeper socio-economic integration of shared development toward the community of common destiny.